Neuronal gamma-aminobutyric acid (GABA) type A receptors undergo cognate ligand chaperoning in the endoplasmic reticulum by endogenous GABA - Wang, Ping; Eshaq, Randa S.; Meshul, Charles K.; Moore, Cynthia; Hood, Rebecca L.; Leidenheimer, Nancy J. (Frontiers in Cellular Neuroscience, 2015)
GABAA receptors mediate fast inhibitory neurotransmission in the brain. Dysfunction of these receptors is associated with various psychiatric/neurological disorders and drugs targeting this receptor are widely used therapeutic agents. Both the efficacy and plasticity of GABAA receptor-mediated neurotransmission depends on the number of surface GABAA receptors. An understudied aspect of receptor cell surface expression is the post-translational regulation of receptor biogenesis within the endoplasmic reticulum (ER). We have previously shown that exogenous GABA can act as a ligand chaperone of recombinant GABAA receptors in the early secretory pathway leading us to now investigate whether endogenous GABA facilitates the biogenesis of GABAA receptors in primary cerebral cortical cultures. In immunofluorescence labeling experiments, we have determined that neurons expressing surface GABAA receptors contain both GABA and its degradative enzyme GABA transaminase (GABA-T). Treatment of neurons with GABA-T inhibitors, a treatment known to increase intracellular GABA levels, decreases the interaction of the receptor with the ER quality control protein calnexin, concomittantly increasing receptor forward-trafficking and plasma membrane insertion. The effect of GABA-T inhibition on the receptor/calnexin interaction is not due to the activation of surface GABAA or GABAB receptors. Consistent with our hypothesis that GABA acts as a cognate ligand chaperone in the ER, immunogold-labeling of rodent brain slices reveals the presence of GABA within the rough ER. The density of this labeling is similar to that present in mitochondria, the organelle in which GABA is degraded. Lastly, the effect of GABA-T inhibition on the receptor/calnexin interaction was prevented by pretreatment with a GABA transporter inhibitor. Together, these data indicate that endogenous GABA acts in the rough ER as a cognate ligand chaperone to facilitate the biogenesis of neuronal GABAA receptors.